THE INFLUENCE OF LIVE STREAMING AND PROMOTION ON SHOPEE ONLINE PRODUCT PURCHASE DECISIONS IN BIREUEN - Nurkhalisah; Riza Bunaiya; Maizatul Akmal; Lailatul Fitri; Munawarah (Universitas Efarina, 2023)
The aim of this research is to determine the effect of live streaming and promotions on online product purchasing decisions (study of shopeee consumers in Bireuen). To get maximum results, the scope of data was obtained from respondents’ answers through questionnaire questions distributed to 90 respondents. The data analysis technique used in this research is multiple linear regression analysis. The research results show that the live streaming variabel (X1) has a significan t effect on purchasing decisions with a value of 0.001 < 0.05 and the promotions variable (X2) has no significan t effect on purchasing decisions with a value of 0.488 < 0.05. Simultaneously live steaming and promotions varibles have a significant effect on purchasing decisions for online Shopee products in Bireuen with a value of 0.001 < 0.05.